ASSESSING THE IMPACT OF ORGANISATIONAL RESTRUCTURING IN AGRICULTURAL COLLEGES: A CASE STUDY OF THE GROOTFONTEIN AGRICULTURAL DEVELOPMENT INSTITUTE (Singaporean Journal of Business Economics and Management, 2014)
Organizational restructuring has become a modern strategy for responding to technological, market and global changes and thus improving the competitiveness of the organisation. Due to technological, global and environmental changes, organisations are forced to change their structure in order to keep up with competitors in the industry. However, changes in the organisation may have dire consequences to employees and also to the organisation as a whole if not implemented properly. The aim of this research was to assess the impact of organisational restructuring in agricultural colleges by focusing on Grootfontein Agricultural Development Institute and to make recommendations to the management of GADI. This research identified the factors that contribute to failure of restructuring and causes of resistance to change by employees. A quantitative research methodology was used to collect data in this study. The total population of 123 respondents was targeted, with 82.9% response rate achieved. A questionnaire instrument with close-ended questions was used to collect data from sample population. This study was significant in that it provided insight on the impact organisational restructuring has on employees and by identifying measures that enable acceptable/appropriate organisational restructuring. The findings of this study reveal 75.5% of the respondents believe that restructuring will improve their working conditions and 64.8 agree that restructuring will not cause instability in the institute. In addition, a high percentage of staff (69.6%) indicated that they are dedicated to work hard to make restructuring successful. However, 61.1% of the staff indicated that there is a lack of adequate internal communication and 52% feeling that the restructuring process is transparent. It was recommended that management improve on communication and to render the process transparent for everyone in the organisation. It was also recommended that leadership should share the vision with the staff if they are to make sure that the strategy meets minimal resistance from employees.